Management of Lead–Acid Battery System in Electric Vehicles - Arun Kumar; Sushil Kumar Agrawal; Rachit Srivastava; Jay Bahadur Singh; Tej Prakash Verma; Palak Gaur (International Journal of Electro-Mechanics and Material Behaviour, 2024)
To determine the lead-acid battery's state of charge in electric vehicles, a novel coulometric method is presented in this article. There are two major problems with the main state of charge algorithms that are currently in use: one defines the state of charge incorrectly for applications involving electric vehicles, and the other uses the accumulator's static performance sub-optimally to estimate its state under dynamic stresses. To address these two shortcomings, we suggest a novel coulometric algorithm that is connected to the electric vehicle's performance. The virtually discharged ampere-hours are determined by using statistical equivalency coefficients on the actual current profile. A considerable improvement with less than 5% errors in all cases examined is shown by the evaluation of this new algorithm on actual discharges.
Keywords: analytical models; electric vehicles; lead corrosion; lead-acid battery; manufacturers